Running out of time? Understanding the consequences of the biological clock for the dynamics of fertility intentions and union formation - Michael Wagner (Demographic Research, 2019)
Background: A considerable proportion of childless women in their late thirties or early forties would still like to have children. The number of men and women whose fertility intentions are potentially influenced by the so-called biological clock for childbearing and who remain involuntarily childless is increasing. Objective: We analyze the short-term dynamics of fertility intentions and partner search among childless, non-partnered men and women aged 35-37. By comparing people in this age group to younger men and women, we investigate whether and how their awareness of the biological clock for childbearing affects their childbearing intentions. Methods: The data stems from the first two waves of the German Panel Analysis of Intimate Relationships and Family Dynamics (pairfam) survey. We selected male and female respondents aged 25-27 (n = 1,073) and 35-37 (n = 369) in Wave 1. Results: Our analyses reveal that fertility intentions are more polarized among men and women aged 35-37 than among their 25-27-year-old counterparts, and are more polarized among women than among men. Finding a partner is shown to positively affect fertility intentions. Our results suggest that people who intensify their fertility intentions are not necessarily successful in finding a partner, which can be seen as a major prerequisite for family formation. Contribution: This is one of the first studies to investigate the fertility intentions of childless men and women whose biological clock is running out. It provides an instructive example for a longitudinal study of the dynamics of life-course-related intentions.